First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Telescopic alluvial fans and pleistocene-holocene temporary lakes in the quebradas del Río Toro and Tastil (Salta, NW Argentina): main sedimentary features - F. Colombo; J. A. Salfity; M. C. Sánchez (Journal of Iberian Geology, 2025)
The Toro and Tastil Quebradas (river valleys) present different terrace-like geoforms made up of deposits of coarse-grained clastic materials. These terraces display convex-upward surfaces, a highly variable distribution, have a small lateral extension and depend on the lithology of the geological basement, which differs significantly along the quebradas . The number of terraces between one area and another indicates that these terraced geoforms should not be ascribed to one single cause, but rather to a variety of factors, i.e. local variations at base-level. The coarse-grained materials of the terraces are usually arranged in roughly horizontal layers that characterize the outcrops. These are interfingered with fine-grained mud-rich materials. The freshwater gastropod remains in the mud-rich materials indicate that they accumulated in lacustrine-like sedimentary environments. These developed from alluvial fans that spread out from the lateral quebradas to occupy the entire main valley (q uebrada) , giving rise to natural dams and temporary lakes upstream. Absolute data obtained by radiocarbon ( 14 C) methods strongly suggest that the alluvial fans were coeval with the temporary lakes in the Upper Pleistocene - Middle Holocene. The El Niño Southern Oscillation (ENSO) effects could have brought about the local variations in base-level that generated the younger temporary lakes, whereas the older ones were probably controlled by precession cycles (at about 21,000 y). The large number of temporary lakes scattered across the region suggests the overlapping of forcing factors at local and regional scales.

The use of a complex tetra-culture alveolar model to study the biological effects induced by gold nanoparticles with different physicochemical properties - Melissa Saibene; Tommaso Serchi; Patrizia Bonfanti; Anita Colombo; Inge Nelissen; Rashi Halder; Jean-Nicolas Audinot; Beatriz Pelaz; Mahmoud G. Soliman; Wolfgang J. Parak; Paride Mantecca; Arno C. Gutleb; et al. (Environmental Toxicology and Pharmacology, 2024)

High-Resolution In Situ Characterization of the Hydrochemical Variability Along the Fluvio-marine Transition of the Río de la Plata Estuary, Argentina - S. Heguilor; E. D. Speranza; L. M. Tatone; C. N. Skorupka; M. C. Migoya; J. C. Colombo (Estuaries and Coasts, 2024)

Correction to: The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The use of biomimetic tools for water quality monitoring: passive samplers versus sentinel organisms - M. Morrone; N. E. Cappelletti; L. M. Tatone; M. J. Astoviza; J. C. Colombo (Environmental Monitoring and Assessment, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Coupled Modeling of Sedimentary Basin and Geomechanics: A Modified Drucker–Prager Cap Model to Describe Rock Compaction in Tectonic Context - N. Guy; D. Colombo; J. Frey; T. Cornu; M. C. Cacas-Stentz (Rock Mechanics and Rock Engineering, 2019)

New Molecular Markers Distinguishing Fonsecaea Agents of Chromoblastomycosis - Gabriela X. Schneider; Renata R. Gomes; Amanda Bombassaro; Kassiely Zamarchi; Morgana F. Voidaleski; Flávia F. Costa; Aniele C. R. Leão; Bruna J. F. S. Lima; Bruna S. Soley; Israella R. Colombo; Giovanna Z. Cândido; Mohammad J. Najafzadeh; et al. (Mycopathologia, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Effects of aerobic exercise training on metabolism of nitric oxide and endothelin-1 in lung parenchyma of rats with pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; R. Siqueira; C. C. Carraro; L. M. Donatti; A. Hickmann; I. E. Litvin; A. E. G. Godoy; A. S. Araujo; R. Colombo; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2017)

Fatty acid alterations in the detritivorous Prochilodus lineatus promoted by opportunistic feeding on sewage discharges in the R ío de la P lata estuary - E. D. Speranza; M. Colombo; L. M. Tatone; N. Cappelletti; M. C. Migoya; J. C. Colombo (Journal of Fish Biology, 2016)
Muscle fatty acid profiles and PCB contents of the detritivorous species Prochilodus lineatus and its diet (stomach contents, settling particles and sediments) were analysed from reference and polluted areas of the Paraná‐Rio de la Plata basin, to evaluate the alterations produced by opportunistic feeding on sewage discharges. Overall muscle fatty acid composition was dominated by saturated and monounsaturated 16 and 18 carbon (18 C‐ FA ) components with reduced long‐chain polyunsaturated fatty acids ( LC‐PUFA ). Compared to sediments, settling particles and stomach contents were enriched in lipids and had a similar fatty acid composition. Opportunistic feeding on sewage detritus at Buenos Aires resulted in enhanced PCB and triglyceride accumulation, with higher proportions of 18 C‐ FA and lower proportions of 16:1 and LC‐PUFA compared to fish from northern pristine reaches of the basin. Mid‐Paraná showed intermediate values reflecting mixing of the North stock with migrating Buenos Aires P. lineatus identified by their lipid and contaminant profile. According to multivariate analyses, this geographical variation of fatty acid composition was strongly influenced by PCB concentration. Prochilodus lineatus assimilates the energy subsidy of sewage inputs through enhanced lipogenesis with dominant 18 C‐ FA and significant amounts of valuable LC‐PUFA . This lipid alteration facilitates the bioaccumulation of PCBs which in turn may reinforce the adipogenic effect of sewage feeding.

The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2016)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Bioaccumulation of dioxin-like PCBs and PBDEs by detritus-feeding fish in the Rio de la Plata estuary, Argentina - N. Cappelletti; E. Speranza; L. Tatone; M. Astoviza; M. C. Migoya; J. C. Colombo (Environmental Science and Pollution Research, 2015)

Direct numerical simulation of fully saturated flow in natural porous media at the pore scale: a comparison of three computational systems - M. Siena; J. D. Hyman; M. Riva; A. Guadagnini; C. L. Winter; P. K. Smolarkiewicz; P. Gouze; S. Sadhukhan; F. Inzoli; G. Guédon; E. Colombo (Computational Geosciences, 2015)

Behavior of Dioxin Like PCBs and PBDEs During Early Diagenesis of Organic Matter in Settling Material and Bottom Sediments from the Sewage Impacted Buenos Aires’ Coastal Area, Argentina - N. Cappelletti; C. N. Skorupka; M. C. Migoya; L. Tatone; M. Astoviza; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2014)

Differential efficiency of two strains of the arbuscular mycorrhizal fungus Rhizophagus irregularis on olive (Olea europaea) plants under two water regimes - M. J. Bompadre; M. C. Rios De Molina; R. P. Colombo; L. Fernandez Bidondo; V. A. Silvani; A. G. Pardo; J. A. Ocampo; A. M. Godeas (Symbiosis, 2013)

Trace Metals in Settling Particles from the Sewage Impacted Buenos Aires Coastal Area in the Río de la Plata Estuary, Argentina - L. M. Tatone; C. Bilos; C. N. Skorupka; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2013)

Migratory behaviour of a dominant detritivorous fish Prochilodus lineatus evaluated by multivariate biochemical and pollutant data - E. D. Speranza; N. Cappelletti; M. C. Migoya; L. M. Tatone; J. C. Colombo (Journal of Fish Biology, 2012)
This paper studies the migration pathways and ranges of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Río de la Plata basin using multivariate analysis of biochemical and pollutant data. Biochemical composition (water, ash, lipids, proteins, carbohydrates, neutral lipids classes and fatty acids), aliphatic hydrocarbons (ALI), polychlorinated biphenyls (PCB), linear alkylbenzenes (LAB) and organochlorine pesticides (OClP) were determined in muscle samples of P. lineatus collected in Metropolitan Buenos Aires, the lower Paraná River (Paraná: 200–1000 km from Buenos Aires) and the middle Paraná and Paraguay Rivers (North: 1000–1400 km north). Biochemical variables and pollutants exhibited large variability [Lipids 1·1–89·5% wet mass; ALI 1·4–413; LABs not detectable (n.d.)–115·2; PCBs n.d.–27·9; OClPs n.d.–11·8 µg g −1 dry mass], due to the contrast of Buenos Aires with North fish. Fish from Buenos Aires were fatty (lipids 24·7 ± 12·3% wet mass), enriched in 18 carbon fatty acids and severely contaminated (ALI 152·4 ± 72·3; LABs 65·1 ± 26·4; PCBs 15·2 ± 6·8; OClPs 1·8 ± 1·9 µg g −1 dry mass mean ± s.d .). In contrast, fish from North were lean (4·1 ± 3·1% wet mass), enriched in long chain (>20 carbons) polyunsaturated fatty acids, with average one to two orders of magnitude lower pollutant levels (ALI 41·2 ± 51·9; PCBs 2·2 ± 3·5; LABs 8·8 ± 21·1; OClPs 0·67 ± 0·75 µg g −1 dry mass mean ± s.d .). Paraná showed intermediate values in all variables, denoting the mixing of different fish stocks. Based on principal component analysis, 14 outliers from 60 North and Paraná samples (representing 26 from 108 individual fish) were identified as pertaining to the Buenos Aires group with very similar lipid and pollutant levels. Data suggest that P. lineatus migrates a highly variable distance, exceeding 800–1000 km in multiple spatial and temporal overlapping ranges. Chemometric analysis of biochemical and pollutant data effectively discriminates fish according to the chemical signature acquired by detritus feeding in pristine and contaminated urban or industrial areas.

Pingüino In-bearing polymetallic vein deposit, Deseado Massif, Patagonia, Argentina: characteristics of mineralization and ore-forming fluids - Sebastián M. Jovic; Diego M. Guido; Isidoro B. Schalamuk; Francisco J. Ríos; Colombo C. G. Tassinari; Clemente Recio (Mineralium Deposita, 2011)

Vertical Fluxes and Accumulation of Trace Metals in Superficial Sediments of the Río de la Plata Estuary, Argentina - L. M. Tatone; C. Bilos; C. N. Skorupka; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2009)

Biochemical composition of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Paraná‐Río de la Plata Basin - E. D. Speranza; J. C. Colombo (Journal of Fish Biology, 2009)
The biochemical composition of muscle, liver and stomach contents of a detritivorous fish Prochilodus lineatus was analysed and compared to settling particles and sediments along pollution gradients over 1500 km of the Río de la Plata Basin to evaluate the effects of anthropogenic discharges in a detritus food chain. The stomach contents of P. lineatus collected in the polluted Metropolitan Buenos Aires coast were enriched in proteins, carbohydrates and lipids, similar to settling particulates collected in the sewer area, and two to five times higher than underlying sediments, supporting the interpretation that P. lineatus feeds on unconsolidated organic flocs freshly decanted from mixed industrial and sewage outfalls. Fish from Buenos Aires had consistently higher standard length ( L S ) and mass ( M T ) slopes ( b = 3·5), condition indexes ( K = 3·01 ± 0·47, mean ± s.d .) and muscle fat content (fat = 23·8 ± 13·8% wet mass, mean ± s.d .) relative to northern fish ( b = 2·7, K = 2·22 ± 0·39, fat = 3·4 ± 3·2% wet mass, respectively), suggesting that sewage‐derived organic matter was an enriched diet, which allowed an enhanced body mass gain and fat accumulation compared to organic‐poor vegetal detritus in the north Paraná area. Buenos Aires fish also showed higher hepato‐somatic indices (mean ± s.d . I H 1·41 ± 0·49 v. 0·70 ± 0·32, respectively), which correlated with their two to three orders of magnitude higher hydrocarbon and polychlorinated biphenyl (PCB) loads, suggesting an enhanced detoxifying metabolism. The northward migration of fatty P. lineatus was evidenced by the presence of clear outliers in the L S and M T relationship, K and fat content along the Paraná River.

Cost-effectiveness of pneumococcal vaccination for prevention of invasive pneumococcal disease in the elderly: an update for 10 Western European countries - S. M. A. A. Evers; A. J. H. A. Ament; G. L. Colombo; H. B. Konradsen; R. R. Reinert; D. Sauerland; K. Wittrup-Jensen; C. Loiseau; D. S. Fedson (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

CT—3D rotational angiography automatic registration: A sensitivity analysis - J. Stancanello; C. Cavedon; P. Francescon; P. Cerveri; G. Ferrigno; F. Causin; F. Colombo (Medical & Biological Engineering & Computing, 2005)

Transpositional behaviour of an Ac/Ds system for reverse genetics in rice - R. Greco; P. B. F. Ouwerkerk; R. J. de Kam; C. Sallaud; C. Favalli; L. Colombo; E. Guiderdoni; A. H. Meijer; J. H. C. Hoge†; A. Pereira (Theoretical and Applied Genetics, 2003)

Global Distribution and Outcomes for Candida Species Causing Invasive Candidiasis: Results from an International Randomized Double-Blind Study of Caspofungin Versus Amphotericin B for the Treatment of Invasive Candidiasis - A. L. Colombo; J. Perfect; M. DiNubile; K. Bartizal; M. Motyl; P. Hicks; R. Lupinacci; C. Sable; N. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Multiple sources for ore-forming fluids in the Neves Corvo VHMS Deposit of the Iberian Pyrite Belt (Portugal): strontium, neodymium and lead isotope evidence - Jorge M. Relvas; Colombo C. Tassinari; José Munhá; Fernando J. Barriga (Mineralium Deposita, 2001)

Early and multiple Ac transpositions in rice suitable for efficient insertional mutagenesis - Raffaella Greco; Pieter B.F. Ouwerkerk; Anke J.C. Taal; Cristina Favalli; Thierry Beguiristain; Pere Puigdomènech; Lucia Colombo; J. Harry C. Hoge; Andy Pereira (Plant Molecular Biology, 2001)

Soil microbial diversity and community structure across a climatic gradient in western Canada - William J. Staddon; Jack T. Trevors; Luc C. Duchesne; Carol a. Colombo (Biodiversity and Conservation, 1998)

Free circulating magnesium and loop diuretics in humans - T. Gozzi; S. Dürler; A. C. Truttman; J. P. Colombo; M. G. Bianchetti (European Journal of Clinical Pharmacology, 1997)